Anti-corrosion coating for highway guardrail and preparation method of anti-corrosion coating

By using an anticorrosion coating combining water-based polyurethane, 2-methyl-4-isothiazolinone-3-one, POSS modified graphene oxide and modified glass flakes on the highway guardrail, the problem of poor water resistance in harsh environments is solved, and the high adhesion, wear resistance and long-term anticorrosion effect of the guardrail is achieved.

CN119708980APending Publication Date: 2025-03-28SHANDONG HI-SPEED NEW BUILDING MATERIALS CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510079431.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-18
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The anti-corrosion coatings of existing highway guardrails have poor water resistance in harsh environments, which leads to corrosion, rust and cracking of the guardrails, affecting protective performance and traffic safety.

Method used

A high-speed guardrail anticorrosion coating is used, and water-based polyurethane is used as the main material, combined with 2-methyl-4-isothiazolinone-3-one, POSS modified graphene oxide and modified glass flakes as preservatives to form a coating with high adhesion and wear resistance. The anticorrosion performance of the coating is enhanced by the modification of graphene oxide and the surface modification of glass flakes.

Benefits of technology

It significantly improves the corrosion resistance of anti-corrosion coatings, enhances the corrosion resistance of guardrails, extends the service life of guardrails, and reduces traffic impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of anticorrosive paint, and particularly discloses anticorrosive paint for highway guardrails and a preparation method of the anticorrosive paint. The invention relates to an anticorrosive coating for highway guardrails. The anticorrosive coating is prepared from the following raw materials in parts by weight: 20 to 50 parts of waterborne polyurethane, 5 to 8 parts of a preservative, 2 to 4 parts of a dispersing agent, 5 to 10 parts of filler, 0.2 to 0.4 part of dibutyl phthalate, 0.1 to 0.3 part of a coalescing agent, 0.2 to 0.4 part of hydroxyethyl cellulose, 0.1 to 0.3 part of a de-foaming agent and 5 to 10 parts of water, the preservative is prepared from 2-methyl-4-isothiazolinone-3-ketone, POSS (Polyhedral Oligomeric Silsesquioxane) modified graphene oxide and modified glass flakes according to the mass ratio of (0.1 to 0.3) to (0.4 to 0.6) to 1. The anticorrosive paint disclosed by the invention is used on the highway guardrail, has long-acting corrosion resistance, high impact resistance, low possibility of generating cracks, good stain resistance and low possibility of influencing the sight induction effect on a driver due to dust accumulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of anti-corrosion coatings, and more specifically, to an anti-corrosion coating for high-speed guardrails and a preparation method thereof. Background Art

[0002] Highway guardrails are important facilities for maintaining highway order and ensuring driving safety. On the one hand, they play a protective role in preventing cars from overturning and running off the highway; on the other hand, they can make the linear contour of the highway smoother and clarify the direction of vehicle vision. At present, highway guardrails are in a harsh outdoor environment and have been subjected to sunlight exposure, wind and rain erosion, seasonal temperature changes and environmental media. The anti-corrosion life of the coating of many guardrails has been greatly shortened, and the decorative appearance has declined, which has seriously reduced the protective performance of the guardrails.

[0003] The anti-corrosion of highway guardrails is generally achieved by hot-dip galvanizing followed by powder electrostatic spraying. After galvanizing and powder spraying, the guardrails have strong corrosion resistance, but the coating process of the above treatment methods is complicated. Because the coating film has a high curing temperature, generally curing at 180-190°C, it consumes a lot of energy and has a high cost for coating preparation; it has strict requirements on the drying conditions of the coating equipment and needs to be painted in a professional painting field, which is not suitable for on-site construction and maintenance of highways.

[0004] In order to alleviate the corrosion of guardrails, spraying anti-corrosion coatings on the guardrails for protection is also a protective method. Existing anti-corrosion coatings are favored by people because of their advantages such as non-flammable, non-toxic, odorless, no need for special construction equipment during construction, no need for heating and curing, no solvent emission and treatment problems, wide application range and many application occasions.

[0005] In the prior art, the Chinese invention patent application document with application number 2021109511623 discloses a water-based polyurethane waterproof coating, which is composed of the following components by weight: 10-15 parts of water, 0.3-0.6 parts of hydroxypropyl methylcellulose, 50-80 parts of water-based polyurethane emulsion, 0.2-0.6 parts of preservatives, 10-30 parts of illite powder, 0.5-1.2 parts of defoaming agent, 10-13 parts of calcium carbonate, 11-16 parts of alumina powder, 5-15 parts of montmorillonite, 4-8 parts of titanium dioxide, 0.2-0.6 parts of antifreeze agent, and 0.3-0.5 parts of thickener. It has strong adhesion and good wear resistance, as well as good solubility and water resistance. With respect to the above-mentioned related technologies, the inventors found that there are hydrophilic groups in the structure of waterborne polyurethane, which can form polar channels in water. Corrosive media can diffuse to the metal surface through these polar channels and cause corrosion to the material. Therefore, the water resistance of waterborne polyurethane coating is slightly poor, which is not conducive to long-term anti-corrosion performance. After corrosion, rust, cracking and other phenomena occur on highway guardrails, road construction and maintenance are generally required in sections, which will affect traffic to a certain extent. Therefore, anti-corrosion coatings are required to have long-term anti-corrosion effects. Summary of the invention

[0006] In order to improve the long-term anti-corrosion effect of the anti-corrosion coating, the present application provides an anti-corrosion coating for a highway guardrail and a preparation method thereof.

[0007] In the first aspect, the present application provides an anti-corrosion coating for a highway guardrail, which adopts the following technical solution: An anticorrosive coating for a highway guardrail comprises the following raw materials in parts by weight: 20-50 parts of waterborne polyurethane, 5-8 parts of preservative, 2-4 parts of dispersant, 5-10 parts of filler, 0.2-0.4 parts of dibutyl phthalate, 0.1-0.3 parts of film-forming aid, 0.2-0.4 parts of hydroxyethyl cellulose, 0.1-0.3 parts of defoamer, and 5-10 parts of water; The preservative comprises 2-methyl-4-isothiazolinone-3-one, POSS-modified graphene oxide and modified glass flakes in a mass ratio of 0.1-0.3:0.4-0.6:1.

[0008] By adopting the above technical scheme, water-based polyurethane is used as the main material, which can reduce organic volatiles, greatly improve environmental protection, and maintain excellent mechanical properties and high adhesion. It is not easy to fall off or crack on the guardrail for a long time; hydroxyethyl cellulose has thickening, suspension, bonding, dispersion and other properties, and dibutyl phthalate is used as a plasticizer to make the coating have good softness, stability, flex resistance and waterproofness; 2-methyl-4-isothiazolinone-3-one in preservatives is a highly active bactericide, and the minimum inhibition concentration for many microorganisms is below 10mg / l. It has a strong killing and inhibitory effect on bacteria, molds, yeasts, and algae, and it is effective at low concentrations. The product has good safety, low toxicity, biodegradable, no teratogenic and mutagenic reactions, and is relatively stable in acidic and oxidizing environments; adding it to the coating can improve the antibacterial and anticorrosive properties of the coating.

[0009] Graphene oxide is filled into the coating. When the coating is cured to form a coating, graphene oxide can play a filling and barrier role, better blocking the path of water molecules and oxygen entering the substrate, and increasing the anti-corrosion performance; the lateral size of the single atomic layer of graphene can extend to tens of microns, which significantly enhances the barrier effect of the coating. The interlayer spacing between graphene nanosheets is at the nanometer level, which can also effectively hinder corrosion interpretation and penetration, thereby improving the physical shielding properties of the coating. However, graphene has poor dispersibility in polymers and is prone to agglomeration. POSS is made by the self-hydrolysis condensation of the organic silicon compound γ-aminopropyltriethoxysilane. The organic-inorganic hybrid cage-type silsesquioxane, POSS and graphene oxide are functionalized through non-covalent bond connection. The cage-like skeleton structure of POSS is embedded between the graphene oxide sheets, producing a steric effect and forming a more stable structure. The three-dimensional structure of POSS can peel off the graphene oxide sheets to a greater extent, improve the dispersion performance of graphene oxide, and increase the tensile strength of the coating. In addition, the rich silicon content in POSS helps to improve the hydrophobic character of the coating, reduce the contact between the corrosive medium and the coating surface, build a barrier between the coating and the corrosive medium, and prevent the occurrence of corrosion.

[0010] Glass flakes can be arranged in parallel and overlapped in water-based polyurethane coatings, which can reduce the shrinkage force of the coating and improve its anti-seepage effect. However, the glass flakes have weak adhesion in water-based polyurethane, which makes it difficult to disperse the glass flakes. Therefore, they are surface modified to increase their dispersibility, and they are overlapped and arranged in an orderly manner inside the coating to construct a flaky shielding skeleton. The staggered overlap between the glass flakes forms a tortuous maze-like protective layer structure, which delays the diffusion of corrosive media to the surface of the guardrail substrate, thereby extending the long-term corrosion resistance of the guardrail.

[0011] Optionally, the preparation method of the POSS modified graphene oxide is: Graphene oxide is dispersed in dimethyl sulfoxide, ultrasonically treated for 10-20 minutes to obtain a dispersion, POSS and cerium chloride heptahydrate are added, the temperature is raised to 180-200°C and stirred for 20-24 hours, filtered, washed, freeze-dried, heated to 700-750°C in a nitrogen atmosphere, and kept warm for 0.5-1 hour. The mass ratio of graphene oxide, POSS and cerium chloride heptahydrate is 1:2-2.3:8-10.

[0012] By adopting the above technical scheme, the amino group on the POSS end group undergoes an amidation reaction with the carboxyl group on the graphene oxide sheet to be grafted, and the ungrafted active functional groups on the graphene oxide contain functional groups, such as hydroxyl, carboxyl and epoxy groups, which make the graphene oxide negatively charged. The cerium ions will interact electrostatically with these functional groups and be tightly adsorbed on the surface of the graphene oxide. In addition, the functional groups such as -OH and -CO on the surface of the graphene oxide will dissociate again. Under certain conditions, the cerium ions adsorbed on the surface will react to form CeO2, thereby reducing the interface energy and surface energy of the graphene oxide, further improving the oxidation Due to the dispersibility of graphene, the graphene with cerium oxide modified on the surface is evenly dispersed in the water-based polyurethane in the coating. When the water, oxygen and chloride ions in the corrosive medium gradually diffuse and penetrate into the coating interface along the micropores and defects in the coating, the POSS-modified graphene oxide with cerium oxide modified on the surface can be evenly dispersed in the water-based polyurethane in the coating and tightly combined with the matrix, acting as a barrier to slow down the intrusion of the medium. The corrosive medium must bypass the POSS-modified graphene oxide-loaded cerium oxide composite material to penetrate into the matrix, and its penetration path is extended, thereby greatly reducing the corrosion rate of the coating and extending the corrosion resistance of the coating.

[0013] Optionally, the preparation method of the modified glass flakes is as follows: after drying the glass flakes, add them to an anhydrous ethanol solution, stir, add triethoxy-1H, 1H, 2H, 2H-tridecafluoro-n-octylsilane, heat to 80-85°C, stir and react for 3-4h, filter, wash, and vacuum dry to obtain pretreated glass flakes, wherein the mass ratio of glass flakes to triethoxy-1H, 1H, 2H, 2H-tridecafluoro-n-octylsilane is 1:2-4; The pretreated glass flakes are dispersed in deionized water, phytic acid is added, reacted at 70-80°C for 7-8h, washed with deionized water until neutral, and dried to obtain modified glass flakes. The mass ratio of the pretreated glass flakes to phytic acid is 1:5-8.

[0014] By adopting the above technical scheme, the glass flakes are mainly composed of silicon dioxide and aluminum oxide, and their surface contains rich Si-OH functional groups. Triethoxy-1H, 1H, 2H, 2H-tridecafluorooctylsilane undergoes hydrolysis reaction in ethanol solution, and a large amount of Si-OH will be produced during the hydrolysis process. Due to the high activity of hydroxyl and epoxy groups, hydroxysilane can not only form silane oligomers through dehydration condensation, but also utilize the dehydration between silicon hydroxyl and hydroxyl groups on the surface of glass flakes to form Si-O-Si bonds, thereby realizing the deposition and coverage of silane oligomers on the surface of glass flakes, and then the surface of glass flakes becomes rough and not smooth. Phytic acid is a substance widely present in plant seeds and grains. It has 6 phosphate groups, is negatively charged, has strong chelation with metal ions, and can form a protective film on the metal surface. The strong chelation of phytic acid is utilized to form a monomolecular film on the surface of the guardrail, which is beneficial to the enhancement of the anti-corrosion performance of the coating.

[0015] Optionally, in the method for preparing the modified glass flakes, zinc nitrate is also added when phytic acid is added, and the mass ratio of zinc nitrate to pretreated glass flakes is 1-1.5:1.

[0016] By adopting the above technical scheme, zinc ions are loaded on glass flakes through electrostatic adsorption, which can improve the anti-corrosion effect of the coating. For example, the change in local pH value after corrosion occurs causes the zinc ions to be released in the coating and form an oxide film, preventing further corrosion. Zinc oxide has good light and heat resistance, and can form coordination compounds with carboxylate ions contained in the coating, thereby reducing the sensitivity of the coating to centering and improving the weather resistance of the coating.

[0017] Optionally, the filler is halloysite nanotubes.

[0018] By adopting the above technical solution, the halloysite nanotubes have a large specific surface area, which helps to enhance the adhesion between the coating and the guardrail substrate. The inner wall and outer surface of the halloysite nanotubes can provide more cross-linking points for the curing process of the coating, thereby improving the hardness and wear resistance of the coating. In addition, the halloysite nanotubes have good thermal stability and chemical stability, enabling them to maintain good performance in high temperature and chemical corrosion environments.

[0019] Optionally, the halloysite nanotubes are treated as follows: Dispersing halloysite in deionized water to obtain a mixed solution, adding zinc acetate solution to the mixed solution, stirring for 4-5 hours, adding ammonium molybdate solution, adjusting the pH to 8, filtering, washing, and drying to obtain modified halloysite; Mix butyl titanate with anhydrous ethanol, add modified halloysite and methyltrichlorosilane, mix well, and dry at 100-120°C.

[0020] The tonnage of long-distance diesel transport vehicles is getting larger and larger. The unburned hydrocarbons and other tiny particles in their exhaust gas are easily adsorbed on the surface of highway guardrails, blackening or polluting highway guardrails, making them dirty and black, reducing their effect on guiding the vehicle's vision, and posing a hidden danger to the safety of vehicles and drivers and passengers. By adopting the above technical scheme, zinc acetate and ammonium molybdate are mixed to form zinc molybdate on halloysite. Ammonium molybdate is a multifunctional material with various morphologies and crystal structures. It has a passivation effect and can generate a passivation layer on the surface of the guardrail. At the same time, it can also generate mixed oxides of molybdenum and iron, which can play an anti-corrosion role. Zinc molybdate particles are fixed on the surface of halloysite, and there is a certain gap between adjacent zinc molybdate particles, which reduces the agglomeration of particles, has a certain inhibitory effect on the penetration of corrosive media, and improves the protective effect of the coating. Finally, titanium dioxide is formed on the surface of halloysite and dissolved, and methyltrichlorosilane is used for hydrophobic addition. The photocatalytic activity of titanium dioxide can effectively decompose the organic components with strong adhesion on the surface of the coating, which will be more conducive to the scouring effect of rain, wind and other external conditions on the surface deposited dirt. The self-cleaning ability of the coating is greatly improved, and the impurities such as dust accumulated on its surface are reduced; combined with cerium oxide in POSS modified graphene oxide, it can effectively enhance the photocatalytic effect of titanium dioxide, so that the coating has better stain resistance, especially under ultraviolet light irradiation, and improve the light self-cleaning performance.

[0021] Optionally, the dispersant is selected from polyethylene glycol 200 or polyethylene glycol 400.

[0022] By adopting the above technical solution, the dispersant can improve the dispersibility and stability of fillers, preservatives and other ingredients in the paint, reduce the attraction and aggregation between particles, reduce the aggregation and sedimentation between particles, and enable the particles to be better dispersed in the paint.

[0023] Optionally, the film-forming aid is at least one of ethylene glycol butyl ether, alkylphenol polyoxyethylene ether, and propylene glycol phenyl ether.

[0024] By adopting the above technical solution, the film-forming aid can help the paint form a continuous and dense coating film during the drying process, improve the leveling, gloss and hardness of the paint, and enhance the decorative effect and durability.

[0025] Optionally, the defoaming agent is a silicone emulsion defoaming agent.

[0026] By adopting the above technical solution, the organosilicon defoamer can destroy the surface tension of the foam, causing it to break and dissipate quickly, thereby playing a role in eliminating and inhibiting the foam and ensuring the density of the coating.

[0027] In the second aspect, the present application provides a method for preparing an anti-corrosion coating for a highway guardrail, using the following technical solution: A method for preparing an anticorrosive coating for a highway guardrail comprises the following steps: uniformly mixing waterborne polyurethane, an anticorrosive agent, a dispersant, a filler, dibutyl phthalate, a film-forming aid, hydroxyethyl cellulose, a defoamer and water to prepare the anticorrosive coating.

[0028] In summary, this application has the following beneficial effects: 1. Since the present application adopts water-based polyurethane as the basic raw material of the coating, it has good environmental performance, excellent mechanical properties, high adhesion, and can form a coating with a dense surface and high adhesion strength on the surface of the guardrail. In addition, 2-methyl-4-isothiazolinone-3-one, POSS-modified graphene oxide and modified glass flakes are used as preservatives to prevent the growth of microorganisms and form a protective barrier to prevent the penetration rate of corrosion components into the guardrail substrate and improve the long-term anti-corrosion effect.

[0029] 2. In the present application, POSS is preferably used to graft-modify graphene oxide to improve the dispersibility of graphene oxide, and cerium chloride heptahydrate is added to form cerium oxide on the surface of graphene oxide through electrostatic adsorption, thereby reducing the interfacial energy of graphene oxide, further improving the dispersion effect of graphene oxide, improving the mechanical properties, and improving the shielding effect of corrosive media.

[0030] 3. In the present application, zinc acetate and ammonium molybdate solution are preferably used to treat the halloysite nanotubes to form zinc molybdate on the halloysite nanotubes to enhance the anti-corrosion ability of the halloysite nanotubes, and titanium dioxide sol is synthesized. At the same time, methyltrichlorosilane is added to improve the hydrophobicity of titanium dioxide and reduce the adhesion of sewage. At the same time, the photocatalytic effect of titanium dioxide is utilized to increase the light self-cleaning ability of the coating. DETAILED DESCRIPTION

[0031] The following examples further illustrate the present application in detail. Preparation Examples 1-3 of POSS-modified graphene oxide

[0032] Preparation Example 1: 250 mg of graphene oxide was dispersed in 500 mL of dimethyl sulfoxide and subjected to ultrasonic treatment for 10 min to obtain a dispersion; POSS and zinc chloride heptahydrate are added to the dispersion, the mass ratio of POSS, zinc chloride heptahydrate and graphene oxide is 2:8:1, the temperature is raised to 180°C, stirred for 24 hours, filtered, repeatedly washed with deionized water, frozen at -70°C for 2 hours, dried under vacuum of 1Pa for 48 hours, and then heated to 700°C in a nitrogen atmosphere and kept warm for 1 hour to obtain POSS-modified graphene oxide, wherein POSS is made by the following method: 45g water, 20mL ice pure, 5mL acetonitrile and 1mL tetraethylammonium hydroxide are mixed, and then 110.5g γ-aminopropyltriethoxysilane is added, stirred at 50°C for 24 hours, excess solvent is removed by rotary evaporation, water and cyclohexane are added to wash in sequence, and freeze-dried to obtain POSS.

[0033] Preparation Example 2: 250 mg of graphene oxide was dispersed in 500 mL of dimethyl sulfoxide and ultrasonically treated for 10 min to obtain a dispersion; POSS and zinc chloride heptahydrate are added to the dispersion, the mass ratio of POSS, zinc chloride heptahydrate and graphene oxide is 2.3:10:1, the temperature is raised to 200°C, stirred for 20 hours, filtered, repeatedly washed with deionized water, frozen at -70°C for 2 hours, dried under vacuum of 1Pa for 48 hours, and then heated to 750°C in a nitrogen atmosphere, kept warm for 0.5 hours to obtain POSS-modified graphene oxide, wherein POSS is made by the following method: 45g water, 20mL ice pure, 5mL acetonitrile and 1mL tetraethylammonium hydroxide are mixed, and then 110.5g γ-aminopropyltriethoxysilane is added, stirred at 50°C for 24 hours, excess solvent is removed by rotary evaporation, water and cyclohexane are added to wash in sequence, and freeze-dried to obtain POSS.

[0034] Preparation Example 3: The difference from Preparation Example 1 is that zinc chloride heptahydrate is not added. Preparation Example 4-9 of Modified Glass Flakes

[0035] Preparation Example 4: (1) After drying, 50 g of glass flakes were added to 500 mL of anhydrous ethanol solution (prepared by mixing ethanol and deionized water in a volume ratio of 4:1), stirred at 500 r / min for 15 min, and then triethoxy-1H, 1H, 2H, 2H-tridecafluoro-n-octylsilane was added. The temperature was raised to 85°C, and the mixture was stirred for reaction for 3 h. The mixture was filtered, repeatedly washed with deionized water and ethanol, and vacuum dried at 40°C to obtain pretreated glass flakes. The mass ratio of glass flakes to triethoxy-1H, 1H, 2H, 2H-tridecafluoro-n-octylsilane was 1:4. (2) Disperse 30 g of pretreated glass flakes into 500 mL of deionized water, add 240 g of phytic acid, and ultrasonically treat for 15 min. Then react at 80 °C for 8 h, wash with deionized water until neutral, and dry at 60 °C to obtain modified glass flakes. The mass ratio of pretreated glass flakes to phytic acid is 1:8.

[0036] Preparation Example 5: (1) After drying, 50 g of glass flakes were added to 500 mL of anhydrous ethanol solution (prepared by mixing ethanol and deionized water in a volume ratio of 4:1), stirred at 500 r / min for 15 min, and then triethoxy-1H, 1H, 2H, 2H-tridecafluoro-n-octylsilane was added. The temperature was raised to 80°C, stirred for reaction for 4 h, filtered, repeatedly washed with deionized water and ethanol, and vacuum dried at 40°C to obtain pretreated glass flakes. The mass ratio of glass flakes to triethoxy-1H, 1H, 2H, 2H-tridecafluoro-n-octylsilane was 1:2. (2) Disperse 30 g of pretreated glass flakes into 500 mL of deionized water, add 150 g of phytic acid, and ultrasonically treat for 15 min. Then react at 70 °C for 7 h, wash with deionized water until neutral, and dry at 60 °C to obtain modified glass flakes. The mass ratio of pretreated glass flakes to phytic acid is 1:5.

[0037] Preparation Example 6: Disperse 50 g of glass flakes into 500 mL of deionized water, add 240 g of phytic acid, ultrasonically treat for 15 min, react at 80 °C for 8 h, wash with deionized water until neutral, and dry at 60 °C to obtain modified glass flakes. The mass ratio of glass flakes to phytic acid is 1:8.

[0038] Preparation Example 7: After drying, 50 g of glass flakes were added to 500 mL of anhydrous ethanol solution (prepared by mixing ethanol and deionized water in a volume ratio of 4:1), and stirred at 500 r / min for 15 min. Triethoxy-1H, 1H, 2H, 2H-tridecafluorooctylsilane was added, and the temperature was raised to 85°C. The mixture was stirred for 3 h, filtered, and repeatedly washed with deionized water and ethanol. The mixture was vacuum dried at 40°C to obtain modified glass flakes. The mass ratio of glass flakes to triethoxy-1H, 1H, 2H, 2H-tridecafluorooctylsilane was 1:4.

[0039] Preparation Example 8: (1) After drying, 50 g of glass flakes were added to 500 mL of anhydrous ethanol solution (prepared by mixing ethanol and deionized water in a volume ratio of 4:1), stirred at 500 r / min for 15 min, and then triethoxy-1H, 1H, 2H, 2H-tridecafluoro-n-octylsilane was added. The temperature was raised to 85°C, and the mixture was stirred for reaction for 3 h. The mixture was filtered, repeatedly washed with deionized water and ethanol, and vacuum dried at 40°C to obtain pretreated glass flakes. The mass ratio of glass flakes to triethoxy-1H, 1H, 2H, 2H-tridecafluoro-n-octylsilane was 1:4. (2) Disperse 30 g of pretreated glass flakes into 500 mL of deionized water, add 240 g of phytic acid and zinc nitrate, and ultrasonically treat for 15 min, react at 80 °C for 8 h, wash with deionized water until neutral, and dry at 60 °C to obtain modified glass flakes. The mass ratio of pretreated glass flakes to phytic acid and zinc nitrate is 1:8:1.5.

[0040] Preparation Example 9: (1) After drying, 50 g of glass flakes were added to 500 mL of anhydrous ethanol solution (prepared by mixing ethanol and deionized water in a volume ratio of 4:1), stirred at 500 r / min for 15 min, and then triethoxy-1H, 1H, 2H, 2H-tridecafluoro-n-octylsilane was added. The temperature was raised to 85°C, and the mixture was stirred for reaction for 3 h. The mixture was filtered, repeatedly washed with deionized water and ethanol, and vacuum dried at 40°C to obtain pretreated glass flakes. The mass ratio of glass flakes to triethoxy-1H, 1H, 2H, 2H-tridecafluoro-n-octylsilane was 1:4. (2) Disperse 30 g of pretreated glass flakes into 500 mL of deionized water, add 240 g of phytic acid and zinc nitrate, and ultrasonically treat for 15 min, react at 80 °C for 8 h, wash with deionized water until neutral, and dry at 60 °C to obtain modified glass flakes. The mass ratio of pretreated glass flakes to phytic acid and zinc nitrate is 1:8:1. Example

[0041] Embodiment 1: A kind of anti-corrosion coating for high-speed guardrail, the raw material dosage is as shown in Table 1, wherein the aqueous polyurethane emulsion is selected from Guangzhou Shanghe New Material Technology Co., Ltd., model WPU-50800, the preservative comprises 2-methyl-4-isothiazolinone-3-one, POSS modified graphene oxide and modified glass flakes in a mass ratio of 0.3:0.6:1, POSS modified graphene oxide is made by Preparation Example 1, and modified glass flakes are made by Preparation Example 4, the dispersant is polyethylene glycol 200, selected from Sanda Chemical, specification is PEG-200, the filler is halloysite nanotubes, selected from Lingshou County Kunna Mineral Products, item number is KN-0453, the film-forming aid is ethylene glycol butyl ether, and the defoamer is a silicone defoamer selected from Jinan Changyingda Chemical Co., Ltd., item number is NR89756.

[0042] The preparation method of the above-mentioned anti-corrosion coating for highway guardrails includes the following steps: mixing water-based polyurethane, preservative, dispersant, filler, dibutyl phthalate, film-forming aid, hydroxyethyl cellulose, defoamer and water evenly to obtain the anti-corrosion coating.

[0043] Table 1 Raw materials and dosage of anticorrosive coatings for high-speed guardrails in Examples 1-3 Raw material / kg Example 1 Example 2 Example 3 Waterborne polyurethane emulsion 50 35 20 preservative 8 6.5 5 Dispersants 4 3 2 filler 10 8 5 Dibutyl phthalate 0.4 0.3 0.2 Film-forming aids 0.3 0.2 0.1 Hydroxyethyl Cellulose 0.4 0.3 0.2 Defoaming agent 0.3 0.2 0.1 water 10 8 5 Example 2-3: An anti-corrosion coating for high-speed guardrails, which differs from Example 1 in that the amounts of raw materials are as shown in Table 1, and the POSS-modified graphene oxide is made from Preparation Example 2, and the modified glass flakes are made from Preparation Example 5.

[0044] Example 4: An anti-corrosion coating for high-speed guardrails, which differs from Example 1 in that the POSS-modified graphene oxide is prepared by Preparation Example 3.

[0045] Example 5: An anti-corrosion coating for highway guardrails. The difference from Example 1 is that the modified glass flakes are made from Preparation Example 6.

[0046] Example 6: An anti-corrosion coating for highway guardrails. The difference from Example 1 is that the modified glass flakes are made from Preparation Example 7.

[0047] Example 7: An anti-corrosion coating for high-speed guardrails. The difference from Example 1 is that the modified glass flakes are made from Preparation Example 8.

[0048] Example 8: An anti-corrosion coating for high-speed guardrails. The difference from Example 1 is that the modified glass flakes are made from Preparation Example 9.

[0049] Example 9: An anticorrosive coating for a highway guardrail, which differs from Example 1 in that the filler halloysite nanotubes are pretreated as follows: 10 kg of halloysite was dispersed in deionized water to obtain a mixed solution with a concentration of 10 wt%, 5 kg of a 0.12 mol / L zinc acetate solution was added to the mixed solution, and after stirring for 5 hours, 5 kg of a 0.015 mol / L ammonium molybdate solution was added, the pH was adjusted to 8, and the mixture was filtered, washed, and dried to obtain modified halloysite; 17 kg of butyl titanate was mixed with 50 kg of anhydrous ethanol, and modified halloysite and 10 kg of methyltrichlorosilane were added, mixed evenly, and dried at 120°C.

[0050] Example 10: An anti-corrosion coating for a highway guardrail, which differs from Example 1 in that the halloysite nanotubes as filler are pretreated as follows: 10 kg of halloysite was dispersed in deionized water to obtain a mixed solution with a concentration of 10 wt%. 5 kg of 0.12 mol / L zinc acetate solution was added to the mixed solution. After stirring for 5 hours, 5 kg of 0.015 mol / L ammonium molybdate solution was added. The pH was adjusted to 8, filtered, washed and dried.

[0051] Example 11: An anti-corrosion coating for a highway guardrail, which differs from Example 1 in that the halloysite nanotubes as filler are pretreated as follows: 10 kg of halloysite dispersion, 17 kg of butyl titanate and 50 kg of anhydrous ethanol were mixed evenly and dried at 120°C. Comparative Example

[0052] Comparative Example 1: An anti-corrosion coating for a highway guardrail, which differs from Example 1 in that an equal amount of unmodified graphene oxide is used instead of POSS-modified graphene oxide.

[0053] Comparative Example 2: An anticorrosive coating for a highway guardrail, which differs from Example 1 in that an equal amount of unmodified glass flakes is used instead of the modified glass flakes. Comparative Example 3: An anti-corrosion coating for a highway guardrail, which differs from Example 1 in that POSS-modified graphene oxide and modified glass flakes are not added. Performance testing

[0054] The anti-corrosion coating was prepared according to the methods in the examples and comparative examples, and the performance was tested according to the following methods. The test results are recorded in Table 3.

[0055] 1. Impact strength test: Use an impact resistance tester and refer to GB / T1732-1993 "Determination of impact resistance of paint film" for testing.

[0056] 2. Salt spray resistance test: Test in accordance with GB / T 1771-2007 "Determination of neutral salt spray resistance of paints and varnishes".

[0057] 3. Determination of anti-fouling performance: Place the copper test plate with the coating side facing downwards in 1:1 fly ash water for 5 seconds, then take it out and dry it naturally in a standard environment for 2 hours. Then, carry out a flushing test according to the test device and test method in GB / T9780-88. Evaluate after 5 cycles. After 6 months, 12 months and 24 months, evaluate the contamination level according to the evaluation standard GB 250-1995: see Table 2 below.

[0058] Table 2 grade Pollution level 0 No pollution, that is, no detectable pollution (gray card level 5) 1 Light pollution, that is, there is just noticeable pollution (gray card level 4) 2 Slight, i.e. more obvious pollution (gray card level 3) 3 Moderate, i.e., obvious contamination (grey card level 2) 4 Severe, i.e. serious pollution (gray card level 1) Table 3 It can be seen from the data in Table 3 that in Example 1, the POSS modified graphene oxide prepared in Preparation Example 1 is used, and the modified glass flakes prepared in Preparation Example 4 are used, and in Example 2, the POSS modified graphene oxide prepared in Preparation Example 2 is used, and the modified glass flakes prepared in Preparation Example 4 are used. The anti-corrosion coatings prepared in Examples 1-3 have high impact strength, long salt spray corrosion resistance time, high corrosion resistance, and certain anti-fouling ability.

[0059] In Example 4, the POSS-modified graphene oxide prepared in Preparation Example 3 was used. In Preparation Example 3, zinc chloride heptahydrate was not added, and zinc oxide could not be loaded in the POSS-modified graphene oxide. It can be seen that the anti-corrosion ability of the coating is significantly reduced.

[0060] In Example 5, modified glass flakes prepared in Preparation Example 6 were used. Compared with Preparation Example 4, triethoxy-1H, 1H, 2H, 2H-tridecafluorooctylsilane was not used in Preparation Example 6, and only phytic acid was used for modification. In Example 6, modified glass flakes prepared in Preparation Example 7 were used. Compared with Preparation Example 4, phytic acid was not used in Preparation Example 7. Compared with Example 1, it can be seen that the salt spray resistance time of the coating is shortened and the long-term anti-corrosion effect is weakened in Examples 5 and 6.

[0061] In Example 7 and Example 8, the modified glass flakes prepared in Preparation Example 8 and Preparation Example 9 are used respectively, to which zinc nitrate is added. Compared with Example 1, the anti-corrosion ability of the coating is enhanced, and the impact resistance and anti-fouling ability are further improved.

[0062] In Example 9, compared with Example 1, the halloysite nanotubes are further pretreated, and the resulting coating has increased impact strength, enhanced corrosion resistance, and increased anti-fouling effect.

[0063] Compared with Example 9, Example 10 does not use butyl titanate and methyltrichlorosilane in the pretreatment of halloysite. Compared with Example 9, Example 11 does not add ammonium molybdate, zinc acetate, etc. in the pretreatment of halloysite. The anti-corrosion ability of the coatings prepared in Examples 10 and 11 is slightly reduced, and the anti-fouling effect is deteriorated.

[0064] Compared with Example 1, the unmodified graphene oxide used in Comparative Example 1 is prone to agglomeration, and the impact resistance and corrosion resistance of the coating are weakened.

[0065] In Comparative Example 2, unmodified glass flakes are used instead of glass flakes. Compared with Example 1, the impact resistance of the coating is reduced and the long-term corrosion resistance is weakened.

[0066] In Comparative Example 3, POSS-modified graphene oxide and modified glass flakes were not added. As shown in Table 3, the impact resistance and anti-corrosion effects of the coating were significantly reduced.

[0067] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An anti-corrosion coating for a highway guardrail, characterized in that: The method comprises the following raw materials in parts by weight: 20-50 parts of waterborne polyurethane, 5-8 parts of preservative, 2-4 parts of dispersant, 5-10 parts of filler, 0.2-0.4 parts of dibutyl phthalate, 0.1-0.3 parts of film-forming aid, 0.2-0.4 parts of hydroxyethyl cellulose, 0.1-0.3 parts of defoamer, and 5-10 parts of water; The preservative comprises 2-methyl-4-isothiazolinone-3-one, POSS-modified graphene oxide and modified glass flakes in a mass ratio of 0.1-0.3:0.4-0.6:

1.

2. The anti-corrosion coating for highway guardrail according to claim 1, characterized in that: The preparation method of the POSS modified graphene oxide: Graphene oxide is dispersed in dimethyl sulfoxide, ultrasonically treated for 10-20 minutes to obtain a dispersion, POSS and cerium chloride heptahydrate are added, the temperature is raised to 180-200°C and stirred for 20-24 hours, filtered, washed, freeze-dried, heated to 700-750°C in a nitrogen atmosphere, and kept warm for 0.5-1 hour. The mass ratio of graphene oxide, POSS and cerium chloride heptahydrate is 1:2-2.3:8-10.

3. The anti-corrosion coating for highway guardrail according to claim 1, characterized in that: The preparation method of the modified glass flakes is as follows: after drying the glass flakes, add them to an anhydrous ethanol solution, stir, add triethoxy-1H, 1H, 2H, 2H-tridecafluoro-n-octylsilane, heat to 80-85° C., stir to react for 3-4 hours, filter, wash, and vacuum dry to obtain pretreated glass flakes, wherein the mass ratio of glass flakes to triethoxy-1H, 1H, 2H, 2H-tridecafluoro-n-octylsilane is 1:2-4; The pretreated glass flakes are dispersed in deionized water, phytic acid is added, reacted at 70-80°C for 7-8h, washed with deionized water until neutral, and dried to obtain modified glass flakes. The mass ratio of the pretreated glass flakes to phytic acid is 1:5-8.

4. The anti-corrosion coating for highway guardrail according to claim 3 is characterized in that: In the method for preparing the modified glass flakes, zinc nitrate is also added when phytic acid is added, and the mass ratio of zinc nitrate to pretreated glass flakes is 1-1.5:

1.

5. The anti-corrosion coating for highway guardrail according to claim 1, characterized in that: The filler is halloysite nanotubes.

6. The anti-corrosion coating for highway guardrail according to claim 5, characterized in that: The halloysite nanotubes are treated as follows: Dispersing halloysite in deionized water to obtain a mixed solution, adding zinc acetate solution to the mixed solution, stirring for 4-5 hours, adding ammonium molybdate solution, adjusting the pH to 8, filtering, washing, and drying to obtain modified halloysite; Mix butyl titanate with anhydrous ethanol, add modified halloysite and methyltrichlorosilane, mix well, and dry at 100-120°C.

7. The anti-corrosion coating for highway guardrail according to claim 1, characterized in that: The dispersant is selected from polyethylene glycol 200 or polyethylene glycol 400; These two substances exist in water-soluble dispersion systems as dispersants, solubilizers, wetting agents and solvents.

8. The anti-corrosion coating for highway guardrail according to claim 1, characterized in that: The film-forming aid is at least one of ethylene glycol butyl ether, alkylphenol polyoxyethylene ether, and propylene glycol phenyl ether.

9. The anti-corrosion coating for highway guardrail according to claim 1, characterized in that: The defoamer is an organosilicon emulsion defoamer.

10. The method for preparing the anticorrosive coating for highway guardrail according to any one of claims 1 to 9, characterized in that: The following steps are involved: The anti-corrosion coating is prepared by uniformly mixing waterborne polyurethane, a preservative, a dispersant, a filler, dibutyl phthalate, a film-forming aid, hydroxyethyl cellulose, a defoamer and water.